The effect of wind on jumping distance in ski jumping depends on jumpers` aerodynamic characteristics - Mikko, V.; Juha, K. (Journal of Biomechanics, 2022)
Several studies have suggested re-evaluation of the wind compensation system (WCS) of the International Ski Federation (FIS). It was introduced in 2009, and since then, the system has been modified considerably, but major shortcomings have still remained. The present study compared the effect of tail/head wind on two reference jumps with different aerodynamic properties (Cd and Cl) during the flight phase. Jump distance and total tangential wind speed data of world cup competitions of the season 2020/2021 were used to analyse the FIS WCS and to offer basic information of wind effects. The correlation between the total tangential wind speed and the jump distance varied strongly among the analysed jumping rounds and showed a big variation in the effect of FIS WCS. According to the computer simulation, a steady head/tail wind during the entire flight phase did not show big difference in jump distance between the jumps with different aerodynamic properties. However, wind had a "reverse" effect on the jumps: when applied to the early flight phase, tail wind increased, and head wind decreased the jumping distance. It seems that the favourable wind conditions at the early flight phase may result in an unfair advantage-disadvantage when the current FIS WCS is used. Therefore, based on the present results, the FIS WCS needs to be further discussed and quality of jumpers` aerodynamic properties re-examined.